(untitled) (Información, cultura y sociedad, 2014)
The implementation of an automated system in information units in countries involved in a process of library conversion, is usually carried out under the influence of different factors. These are defined as external or contextual, when they refer to the library environment conditions and as internal when they relate to the library structure and intrinsic functioning. This work intends to carry out a qualitative research on the basis of the categories mentioned above, from specific cases selected from the library literature. Its aim is to describe and assess the incidence levels of these factors in the automation of information units. In conclusion, the present analysis reveals the preminence of internal factors (technical and of library management and policy) over those identified as external. It also shows that instances associated with the project planning and human resources training, appear as the most relevant indicator in the stage of results evaluation.